Evaluation of the Pre-Service Teacher Professional Education Using CIPP Model - Sefni Novita Sari; Dian Laili Rahmawati; Rahmayuni Alfajri; Friyatmi Friyatmi; Dessi Susanti (Universitas Negeri Padang, 2024)
The evaluation of the Professional Teacher Education Program for Social Science subjects at the State University of Padang uses the Context, Input, Process, and Product (CIPP) evaluation model. The context evaluation understands the background, needs, and regulations of the UNP Social Studies PPG. Input evaluation evaluates various aspects of the institution, including the curriculum, facilities, funding, and qualifications of lecturers and students. The process stage analyzes the overall implementation of the program. The product stage evaluates the knowledge, skills, results, and impacts of the PPG Social Studies program. Through interviews and questionnaires, the study method used both qualitative and quantitative methods. This study involved 184 pre-service PPG students in the field of social studies at UNP, recruited for the 2023/2024 academic year using the purposive sample approach. The strategies for analyzing qualitative data include: (1) data collection, (2) data reduction, (3) data presentation, and (4) verification and conclusion drawing. Quantitative descriptive analysis was done with SPSS version 25. The overall outcomes of the study, as determined by the CIPP model, fall within the good category. Students in this program have a good understanding of the educational context and are ready to enter the school environment. The program also ran well and met the set objectives, with adequate support to gradually develop students' teaching skills.